Neurotrauma and Repair Research: Traumatic Brain Injury (TBI) and its Treatments. (January 2013) - Algattas, Hanna; Huang, Jason H.
Traumatic brain injury (TBI) affects a growing portion of the population and continues to take national spotlight with advances in imaging technology and understanding of long-term effects. However, there is large variance in TBI treatment protocols due to injury variability and lack of both mechanistic understanding and strong treatment recommendations. Recent practice suggests three disparate treatment approaches, all which aim at promoting neuroprotection after TBI, show promise: immediate hypothermia, hyperbaric oxygen, and progesterone supplementation. The research is controversial at times, yet there are abundant opportunities to develop the technology behind hypothermia and hyperbaric oxygen treatments which would surely aid in aligning the current data. Additionally, while progesterone has already been packaged in nanoparticle form it may benefit from continued formulation and administration research. The treatments and the avenues for improvement are reviewed in the present paper.